Galicyjskie wzorce polonistycznych zajęć pozalekcyjnych = Extracurricular lessons of Polish in Galician junior high-schools - Prościak, Beata (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The author presents the contents and significance of extracurricular lessons of Polish in Galician junior high-schools and aspires to demonstrate the present importance of the experiences.
Keywords: Galicja; szkolnictwo